THE FEATURES OF PSYCHOLOGICAL FACTORS DETERMINING THE WORKABILITY OF HUMAN - Davtyan , A. G. (Արդի հոգեբանություն, 2025)
During the working process not only professional but also some amount of personal qualities are being reconstructed, modified and developed. The efficiency of the activity is due to several factors, which are reflected by the working capacity of the body. In some working conditions weak physiological readiness to work can be replaced with strong work motivation which itself leads to the increment of productivity.